DIPLOMASI INDONESIA MELALUI KAMPANYE WONDERFUL INDONESIA DALAM MENINGKATKAN PARIWISATA INDONESIA DI DUNIA INTERNASIONAL TAHUN 2011-2015 - Gusti Idriasih; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research analyze about Indonesian Diplomacy by Wonderful Indonesia Campaign to increase Indonesia tourism sector in international world, especially during 2011-2015. One of Indonesian Government efforts to increase the tourism sector is by launch a country branding to promote the Indonesia’s wonderful tourism potential. On January 2011, the government under the Culture and Tourism Minister officially launched the new tourism country branding “Wonderful Indonesia” replaced the previous branding “Visit Indonesia”.This research shows how the diplomacy of Indonesia which involves many parties to promote the Indonesia tourism sector by Wonderful Indonesia campaign. As the world largest archipelago and a country with mega-biodiversity, promotion is an Indonesia government priority to shows the world that Indonesia has many destinations supporting the tourism sector and to create the Indonesia good image in international world.The data were collected from many sources like books, journals, and websites that can support this research. In this research, the reseacher uses neorealism perspective to describe the Indonesian Diplomacy by Wonderful Indonesia Campaign. This research will be analyzed and explained by Multi Track Diplomacy. It means that Indonesia targets in tourism sector not only pursued by the government, but also by cooperating with many non-governmental stakeholders.Keywords : Soft Diplomacy, Multi Track Diplomacy, Wonderful Indonesia, Country Branding, and Tourism